1971
DOI: 10.1104/pp.48.2.208
|View full text |Cite
|
Sign up to set email alerts
|

Abscission

Abstract: The role of ethylene-mediated reduction of auxin transport in natural and ethylene-induced leaf abscission was studied in the cotton (Gossypium hirsutum L., cv. Stoneville 213) cotyledonary leaf system. The threshold level of ethylene required to cause abscission of intact leaves was between 0.08 and 1 u/l with abscission generally occurring 12 to 24 hours following ethylene fumigation. The threshold level of ethylene required to reduce the auxin transport capacity in the cotyledonary petiole paralleled that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
40
0
1

Year Published

1974
1974
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(50 citation statements)
references
References 33 publications
(45 reference statements)
9
40
0
1
Order By: Relevance
“…Auxin transport capacity was reduced 79% after 48 hr when the entire leaf was treated with ethylene but only 42% when the leaf blade remained in air. By keeping the leaf blade in air the petiole was presumably provided with auxin, which, as previously reported (9,33), reduces the ability of ethylene to inhibit auxin transport. In contrast to ethylene, DPX1840 inhibited auxin transport over 90% within 4 hr under all treatment conditions (data not shown).…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Auxin transport capacity was reduced 79% after 48 hr when the entire leaf was treated with ethylene but only 42% when the leaf blade remained in air. By keeping the leaf blade in air the petiole was presumably provided with auxin, which, as previously reported (9,33), reduces the ability of ethylene to inhibit auxin transport. In contrast to ethylene, DPX1840 inhibited auxin transport over 90% within 4 hr under all treatment conditions (data not shown).…”
Section: Resultsmentioning
confidence: 72%
“…Naphthaleneacetic acid clearly blocks the effect(s) of ethylene in the leaf blade just as it does in the petiole and abscission zone (9,27). It is well established (9,11) that ethylene at the concentration used in this study severely reduces auxin transport in the petiole of cotton within 24 hr. Therefore, the question arises as to why ethylene did not fulfill the same role as DPX1840 since the petiole was exposed to the gas for 7 days.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…First, three appropriate species were tested. Both beans and cotton produce ethylene which regulates, at least in part, natural leaf abscission (7,20). Both species demonstrated the common acceleration of ethylene release from detached leaves when they are air dried ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, metabolic acclimation to low oxygen improves the tolerance of roots to anoxia (29). ' The gaseous plant hormone, ethylene, is associated with a wide variety of responses in higher plant cells (3). In earlier reports we showed that aerenchyma formation in adventitious (nodal) roots of maize by cell lysis is induced by a partial oxygen deficiency (hypoxia) and is closely related to enhanced endogenous concentrations of ethylene (1 1).…”
mentioning
confidence: 99%